Native Language Phonological Skills in Low‐Proficiency Second Language Learners. Issue 1 (7th January 2014) - Borodkin, Katy; Faust, Miriam
<x xml:space="preserve">Abstract</x> This study investigated the link between low second language performance and difficulties with native language phonological processing. Participants were native Hebrew speakers, 19–31 years of age, who learned English as a second language in a school setting. Individuals with dyslexia performed below high‐proficiency second language learners on each of four tasks assessing native language phonological processing, whereas low‐proficiency second language learners were disadvantaged compared to high‐proficiency second language learners on only two of the tasks: pseudoword repetition and tip‐of‐the‐tongue naming. These results indicate that both individuals with dyslexia and low‐proficiency second language learners have a weakness in native language phonological processing. The weakness in low‐proficiency second language learners, however, is evident in a more limited set of skills compared to individuals with dyslexia.